Haplosclerida (Porifera: Demospongiae) from the coast of Maranhão State, Brazil, Southwestern Atlantic - Campos, Maurício; Mothes, Beatriz; Eckert, Rafael; van Soest, Rob W.m. (Zootaxa, 2005)
This work deals with haplosclerid sponges off the coast of Maranhão State, northeastern coast of Brazilian shelf (southwestern Atlantic). A new species is described, Haliclona (Halichoclona) lernerae. Four species are recorded for the first time for the Brazilian coast: Amphimedon caribica (Pulitzer-Finali, 1986); Niphates lutea Lehnert & Van Soest, 1999; Neopetrosia subtriangularis (Duchassaing, 1850) and Petrosia (Petrosia) weinbergi Van Soest, 1980. Three species were recollected from the southwestern Atlantic and have their geographic distribution extended on the Brazilian coast: Callyspongia (Cladochalina) vaginalis (Duchassaing & Michelotti, 1864), Oceanapia bartschi (De Laubenfels, 1934) and Xestospongia muta (Schmidt, 1870). Two species were collected for the first time from the Maranhão State Coast: Niphates erecta Duchassaing & Michelotti, 1864 and Neopetrosia proxima (Duchassaing & Michelotti, 1864). A taxonomic study of those samples is given, including description, illustrations and geographic distribution.